(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In this research paper efforts have been made toexplore various factors which affect the behaviour of consumers in a retailoutlet. A random sample of respondents visiting retail outlets has beenconsidered for the present study. The paper mainly focuses towards variousfactors which affects the decision of the consumer in the store while theyvisit there for shopping. So, this research is mainly concerned with thebehaviour of the consumer and the various factors which are of enormousimportance in converting the footfall within the stores. The paper also intendsto recommend some feasible and viable strategies to be followed by retailoutlets to maximize the percentage of conversion.